MOTIF MENGGUNAKAN APLIKASI LINE WEBTOON DI KALANGAN KOMUNITAS COMICOTOPIA BALI - Gesiradja, Asriyanti Saputri; Alit Suryawati, I Gusti Agung; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT LINE Webtoon is a form of media convergence, which is the transformation of conventional comics into digital form using the Internet. Since the launch, LINE Webtoon has received positive response by the public, especially Indonesia.This research aims to find out the motives of comic lovers community satisfaction by using this application LINE Webtoon, reference by the categories motives proposed by McQuail which is motive of information, motives of personal identity, motive of integration and motive entertainment. The theory used in this study is the theory of Uses and. This research uses quantitative quantitative methods with descriptive research types. Data retrieval techniques are questionnaires. The results of the research show that the motives of entertainment are in the high category, while information motives are in the low category. Keywords: digital Comic, Motive, LINE Webtoon